Political Connections and Financial Constraints : Evidence from Transition Countries - Bussolo, Maurizio; de Nicola, Francesca; Panizza, Ugo; Varghese, Richard (World Bank, Washington, DC, 2019)
This paper examines whether political connections ease financial constraints faced by firms. Using firm-level data from six Central and Eastern European economies, the paper shows that politically connected firms: (i) have high levels of leverage, (ii) have low levels of profitability, (iii) are less capitalized, (iv) have low marginal productivity of capital, and (v) do not invest more than unconnected firms. Next, the paper shows that connected firms borrow more because they have easier access to credit and that political connections lead to a misallocation of capital. The results are consistent with the idea that political connections distort capital allocation and may have welfare costs.